Suppression of wetting-induced percolation-to-droplet transition in near-critical polymer blend films by nanoparticles. Issue 7 (18th January 2016) - Jiang, Xiaolian; Xi, Shuting; Xia, Tian; Kong, Miqiu; Yang, Qi; Li, Guangxian; Huang, Yajiang
Abstract : A novel percolation-to-droplet transition (PDT) caused by selective wetting, which can be suppressed by using nanoscale particles, is identified in near-critical polymer blend films. Abstract : A new kind of percolation-to-droplet transition (PDT) caused by selective wetting was identified in near-critical polymer blend films. Nanoscale particles proved to possess superior ability in suppressing this morphological transition.